The Model of Structural and Functional Organization of the Psycho- Semantic System of Family Purposefulness - Natalia V. Nozikova (Rossijskij psihologičeskij žurnal., 2016)
The paper presents the empirical model of structural and functional organization of family psycho-semantic integrity. The hypothesis is that the theoretical model of the analysis of psycho-semantic integrity makes it possible to reveal principles of structural and functional organization of the psycho-semantic system of family purposefulness. The sample included (a) 15–18 year-old young men and women (secondary school students) and (b) 20–44 year-old men and women (married and raising children). I. L. Solomin’s Osgood program of the semantic differential method modified variant was used. In order to assess the technique of semantic differential by respondents, a modification of the principle of formation of the list of concepts was carried out. In accordance with the research objective the authors chose: (a) categories of concepts related to family life (people and groups, events, activities, and ideal representation); (b) concepts-markers defining basic values, life stages, people, groups of people, relations to them, gender concepts, activities and types of activity, and emotional experiences and events. General principles of psycho-semantic analysis and the results of the study of psycho-semantic integrity enabled authors to propose a theoretical model of structural and functional analysis of the psycho-semantic system. This model formed the basis for the comparative analysis of the psycho-semantic system depending on factors of gender, age, and marital status of the respondents. The carried out study made it possible to distinguish the following principles of the psycho-semantic model of the system of family purposefulness: 1) principle of the semantic criterion of the organization of integrity; 2) principle of structural organization, involving the analysis of structural and qualitative characteristics of integrity, subsystem clusters of concepts performing specific functional tasks, and components - concepts of the considered area of life; 3) principle of functional purposefulness determined by dominating values, which depend on factors of gender, age, and marital status; 4) principle of the functional organization of psycho-semantic integrity. The findings are of direct practical relevance in the practice of family psychology.